Does Cross-Listing Lead to Functional Convergence? Empirical Evidence - Ayyagari, Meghana (World Bank, Washington, D.C., 2013)
The author examines the effect of legal bonding on ownership and control structures of foreign firms cross-listing in the United States. Contrary to the predictions of corporate governance convergence theories, there is little evidence of convergence-related migration to a dispersed ownership structure on cross-listing. She finds that rather than as a means to change their governance structure, foreign firms use American Depository Receipts as a vehicle to sell control blocks, often to a new foreign owner. Firms that cross-list and sell stakes to domestic owners are from large economies with high stock market liquidity. In contrast, firm-level characteristics are more important predictors of a control change to a foreign owner. Cross-listing firms that sell control blocks to foreigners tend to be smaller, have low levels of debt, and have a high foreign income growth rate. The post cross-listing performance of firms that undergo a control change is also different from firms that do not experience a control change.